Peningkatan Kadar Lipoprotein-Associated Phospholipase A2 Meningkatkan Kejadian Stroke Iskemik Akut - Syarif Indra (Universitas Baiturrahmah, 2021)
Introduction: Stroke is a major health problem in the world, and associated with mortality, disability, and economic burden. Stroke is the second leading cause of death in the world after heart disease and cause of disability in adults. Several recent studies show that levels of Lp-PLA2 contribute to high serum lead to ischemic stroke, whereas some others do not get the association. Aims: studies an association between serum Lp-PLA2 with incident ischemic stroke. Method: This study is a descriptive analytic comparative with cross sectional design in the Neurology ward RS. DR. M. Djamil Padang between October 2013 to April 2014 with total of 88 subjects consisting of 44 subjects ischemic stroke patients and 44 healthy control group who participated in the study. Statistical analysis is used parametric test with unpaired t test, test for normality with the Kolmogorov-Smirnov test, and logistic regression analysis. Result: P value 0.05 was considered statistically significant. The mean age of subjects in the group of ischemic stroke patients was 57.30 ±8.86 years old. Female in patients with ischemic stroke group was 23 people (52,3%). Mean levels of Lp-PLA2 serum in patiens with ischemic stroke group was 103.49±48.00 ng/mL. A significan association between serum levels of Lp-PLA2 with incident ischemic stroke with p<0.05. Conclusion: There was a significant relation in elevation of serum Lp-PLA2 levels with incident of ischemic stroke.